2019
DOI: 10.1186/s40425-019-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and immune checkpoint inhibitors as therapies for hepatocellular carcinoma: current knowledge and future research directions

Abstract: Hepatocellular carcinoma (HCC) is the second deadliest cancer worldwide, due to its high incidence and poor prognosis. Frequent initial presentation at advanced stages along with impaired liver function limit the use of a broad therapeutic arsenal in patients with HCC. Although main HCC oncogenic drivers have been deciphered in recent years (TERT, TP53, CTNNB1 mutations, miR122 and CDKN2A silencing), therapeutic applications derived from this molecular knowledge are still limited. Given its high vascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
126
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 77 publications
0
126
1
1
Order By: Relevance
“…Clinical evidence suggests that anti-VEGF agents synergize with immune checkpoint inhibitors to improve disease control and overall survival in different cancer types, an effect associated with larger numbers of effector T cells in the TME. 4 Although an increase in TIL might be linked to transient normalization of the tumor vasculature, VEGF blockade can also create an immunodominant TME by impeding VEGF immunosuppressive activities. 4 We reported that perivascular SOD3 triggers a program that simultaneously induces vascular normalization and T cell infiltration, thus linking these two processes unequivocally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical evidence suggests that anti-VEGF agents synergize with immune checkpoint inhibitors to improve disease control and overall survival in different cancer types, an effect associated with larger numbers of effector T cells in the TME. 4 Although an increase in TIL might be linked to transient normalization of the tumor vasculature, VEGF blockade can also create an immunodominant TME by impeding VEGF immunosuppressive activities. 4 We reported that perivascular SOD3 triggers a program that simultaneously induces vascular normalization and T cell infiltration, thus linking these two processes unequivocally.…”
mentioning
confidence: 99%
“…4 Although an increase in TIL might be linked to transient normalization of the tumor vasculature, VEGF blockade can also create an immunodominant TME by impeding VEGF immunosuppressive activities. 4 We reported that perivascular SOD3 triggers a program that simultaneously induces vascular normalization and T cell infiltration, thus linking these two processes unequivocally. 5,6 The anti-oxidant enzyme SOD3 is usually downregulated in tumors, which suggests that its loss is advantageous for cancer progression.…”
mentioning
confidence: 99%
“…Recently, a study was published in Nature by Alspach et al [19] , in which they gave more weight to the role of helper CD4 lymphocytes in immuno-oncology over the usual culprit, i.e., CD8 killer cells. Whether V5 more affects CD4 rather than CD8 cells remains to be established; it is likely that both subpopulations are required, and that other subsets of immune cells are also critically involved [20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of immune checkpoints (PD-1 alone or with CTLA-4) has also become an option recently, but the vast majority of patients (~70%) still do not respond to immunotherapy, even when combined with antiangiogenic drugs. Therefore, there is a clear need for more efficacious strategies for HCC treatment [9].…”
Section: Introductionmentioning
confidence: 99%